Nigeria - An Economic Analysis of Natural Resources Sustainability : Land Tenure and Land Degradation Issues - World Bank (Washington, DC, 2012)
The scope and urgency of the threats to Nigeria's rural land are no secret. In 2005, a working group dedicated to formulating a national agricultural land policy began the process with a comprehensive articulation of the challenges facing Nigeria's agricultural land. The litany included recognition that: 1) agricultural land use in the country has been unsustainable, resulting in no fewer than eleven types of extensive land degradation and significant degradation of water resources; 2) the country has not classified its land - including its prime agricultural land - according to its use capabilities, and thus has no foundation for allocating land among uses or creating the mechanisms and processes for such allocation; 3) the majority of Nigeria's farmers are smallholders relying on subsistence-level cultivation practices; 4) the country's agricultural labor pool is shrinking, and practices that promote better conservation of natural resources have been too limited; and 5) the rural areas of the country lack of basic and necessary infrastructure, including roads, water, and health and educational facilities. This part of the report analyzes how Nigeria's land policy and legal framework can support efforts to meet the country's expressed land policy goal of sustainable productivity and additional goals of equity and conflict avoidance. Section two makes a brief overview of the links between land tenure systems, agricultural productivity, and equity; section three makes a review of the customary and formal land tenure systems in Nigeria, and section four makes the same for the formal land tenure system. Section five summarizes the existing legal framework and its impact on productivity, equity and potential for conflict. The last section concludes with specific recommendations for unlocking the potential in the country's rural land to meet the needs of its entire people.